Relationship marketing management of RTE with service consumers - Feng, Xin (Харківський національний автомобільно-дорожній університет, 2024)
The qualification work enhances the theoretical principles of managing relationship marketing between an RTE and its service consumers. A definition of "relationship marketing between an RTE and its consumers" is proposed. Methodological foundations for assessing the level of relationships between an RTE and its consumers have been developed. Unlike existing approaches, these are based on a three-dimensional matrix considering the RTE's attitude toward consumer relationships, the consumer's attitude toward the RTE, and the prospects of these relationships. Strategies for managing relationships with each consumer group have been developed, alongside recommendations for improving customer loyalty. Various loyalty programs have been proposed to strengthen consumer commitment and interaction with the RTE. Forecast assumptions for the development of the research object - formation of service consumer relationships within the enterprise, taking into account the mutual attitudes of the enterprise and the consumer, as well as the prospects for relationship development.
Keywords: relationship marketing; relationships; customers; management; management system; interaction; evaluation; loyalty program